Isocratic RP-HPLC Method for Simultaneous Separation and Estimation of Zofenopril and Hydrochlorthiazide in Pharmaceutical Dosage Forms. Issue 2 (2012) - Devika, G. S.; Sudhakar, M.; Rao, J. Venkateshwara
Abstract : A simple, rapid, sensitive and accurate isocratic reverse phase high performance liquid chromatographic (RP-HPLC) method has been developed and subsequently validated for the simultaneous determination of Zofenopril and Hydrochlorthiazide in combined dosage form. Chromatographic separation of the two drugs was performed on a Purospher BDS C18 column (250 mm × 4.6 mm id, 5 μm particle size). The mobile phase comprising of acetonitrile methanol: 0.02M NaH2 2PO4 buffer (40:20:40) was delivered at a flow rate of 1.0mL/min. The pH of the mobile phase is adjusted to 7.2 with Sodium hydroxide solution. Detection was performed at 245 nm.The separation was completed within 10 min and the retention time of hydrochlorthiazide is 4.62 and Zofenopril is 6.86 min respectively. Calibration curves were linear with R 2 between 0.99-1.0 over a concentration range of 100-600 μg/ml for Zofenopril calcium and 50-300 μg/ml for hydrochlorthiazide..The developed method was successfully applied to determi